TRABAJOS DE FIN DE GRADO SOBRE HUMANIDADES EN TRES ESTUDIOS DE CIENCIAS DE LA SALUD. - CAMBRA-BADII, Irene; FARRÉ, Magí; PÉREZ, Jorge (Journal of Medicine & Movies / Revista de Medicina y Cine, 2024)
Educational authorities recommend the incorporation of humanities into the curricula of health science programs to enhance the education of their graduates. The aim of this study was to determine the number of final degree projects focused on humanities in three health science programs. All final degree projects completed during 7 cohorts (2013-2020) in the Human Biology and Medicine programs at Pompeu Fabra University, and during 6 cohorts (2015-2021) in the Medicine program at an affiliated teaching unit of the Autonomous University of Barcelona were reviewed. The volume of humanities-based final degree projects was modest in the two Medicine programs (less than 10%) and higher in the Human Biology program (15.5%). The majority of the projects addressed topics of social interest. Additionally, in all three programs, projects were carried out on issues affecting the students themselves, as well as on teaching-related subjects and the use of movies or TV series to enhance learning. Encouragement is given to cultivate a stronger interest in pursuing undergraduate projects centered around humanistic themes.